Ovis dalli Nelson 1884 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Ovis dalli Nelson, 1884. Proc. U.S. Nat. Mus., 7: 13. TYPE LOCALITY: Alaska, West bank of Yukon River. DISTRIBUTION: Alaska to N. British Columbia and W. Mackenzie (Canada). ISIS NUMBER: 5301419009041003001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Artiodactyla, pp. 315-343 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 339, DOI: 10.5281/zenodo.7352976